PENDIDIKAN ISLAM PADA MASA RASULLAH SAW. (PERIODE MEKAH DAN MADINAH) - Muhammad Ihsan (Paedagogia: Jurnal Pendidikan, 2019)
Islamic education today cannot be separated from Islamic education in Islamic classical era. The Prophet Muhammad has served as a central figure of Islamic education from Islamic classical era to modern Era. The implementation of Islamic education in the time of the Prophet Muhammad can be categorized into Meccan period and Medina Period. In Meccan period, the prophet put emphasis on tawhid, who used to adhare to politism, to adhare to monotism, that is to believe in Allah the only God. The strategy of education employed by the prophet was secret in nature. Initially, he conducated Islamic education amongst the members of his family and his companions then to more extended cummunity. In Mecca, the Prophet made the house of al-Arqam ibn Abi Al-Arqam, as the centre of Islamic education. In Medinan period, the prophet conducted more complex Islamic education than that he did in Mecca. Islamic education conducted to covered (a) Islamic brotherhood; (b) social walfare education; and (c) nation defence education. In this period, it was mosque that served as the centre of Islamic education.